PROBLEMATIKA PENGGUNAAN MEDIA GOOGLE CLASSROOM PADA PEMBELAJARAN MENULIS KARYA ILMIAH DI KELAS XI SMK SWASTA MARISI MEDAN - Sarma Panggabean; Pontas Jamaluddin Sitorus; Santa Monica Sinaga (Jurnal Inovasi Penelitian, 2021)
This study is expected to describe the types of problems/difficulties experienced by students when learning to write scientific papers is carried out using Google Classroom media. This study uses a descriptive quantitative approach because it wants to describe the results of the data that has been collected, namely the problems of using Google Classroom media in learning to write scientific papers. The sample in this study was 64 students of class XI SMK Marisi Medan majoring in Office Governance Automation and Institutional Financial Accounting. As a result, students have difficulty understanding the material because learning is only done using Google Classroom media, besides that students also have difficulty using Google Classroom media because they are using this media for the first time. There are two factors that cause difficulties for these students, namely internal factors such as students lack of interest in participating in learning because they feel bored, and external factors such as lack of guidance and support from parents. The most dominant problem that occurs is the unavailability of quotas and students feel they have no interest in participating in learning because they do not understand the learning material presented.